Strengthening The Implementation of E-Court-Based Judiciary As A Legal Protection In The Implementation of E-Litigation-Based Trials - Juliani Paramitha Yoesuf; Fery Ramadhansyah; Sinta Elviyanti; Ade Salamah (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
E-Court has been implemented in all courts in Indonesia. However, among legal experts, implementing electronic-based trials (e-litigation) raises pros and cons, especially when parties must attend the trial. This situation is interesting and must be investigated immediately to create legal certainty. The issues that will be examined are: 1) the appropriateness of electronic trial arrangements (e-litigation) based on Supreme Court Regulation of the Republic of Indonesia Number 7 of 2022 dated October 10th2020, and 2) the form of strengthening the implementation of electronic trials (E-Litigation) in e-court. The research method used in this research is normative-empirical legal research, also known as applied law research. The data types used to study normative-empirical legal research are primary and secondary. The results show that 1) Electronic trial arrangements (e-litigation) based on the Supreme Court Regulation of the Republic of Indonesia Number 7 of 2022 concerning the Administration of Cases and Trials in Electronic Trial (e-litigation) are appropriate. However, this regulation still needs to be improved and strengthened so that the litigants as e-court users can obtain law enforcement and justice. 2) The regulation of e-courts needs to be strengthened, as the law must absorb what the community wants in judicial practice. Policy strengthening regarding e-court can be carried out through a) amendments to the Judicial Powers Act, primarily related to regulations for the electronic announcement of decisions as a consequence of legal reforms; b) establishment of the law on the implementation of e-court and e-Litigation; c) establishment of a new Perma to strengthen Perma No. 7 of 2022.